Study of the anti-inflammatory and immunomodulatory activity of bovine placental extract (Mongolian Journal of Agricultural Sciences, 2019)
Many scientists study structure and charagterization of placenta and experimenting on their biological activity, due to develop new drugs and biopreparation for human and animal health. The present study aimed to isolate bovine placental lactogen from placenta by semi purification method and determine antioxidant, anti-inflamatory activity and effect on immune responses was also investigation.Semi purified protein was separated  by gel-chromatographic method using 3 methods of tissue homogenizations of placental tissue using distilled water, phosphate buffer saline and Tris-HCl, by use of 4 methods of protein extraction and precipitation with distilled water, sulfate ammonium salt and organic solvents, such as ethanol and acetone.Antioxidant activity of semi purified  protein was measured by DPPH method, effect on immunity was investigated by using MTT assay kit, and anti-inflammatory activity was measured by using 1 % carrageenan-induced rat paw edema models. Measurements of total proteins which were homogenized in PBS, followed by acetone precipitation is 6217.5 µg/ml is the highest and homogenized in PBS, followed by sulfate ammonium salt precipitation is 1477.4 µg/ml is the lowest concentration.Bovine placental extract DPPH radical scavenging activity was 55.1±1.2% and rutin was 67.1±1.2% but results of immunity experiment demonstrated splenocyte division in placental extract added medium for stimulation index 1.45 or splenocyte culture increased by 1.5 times than as compared to those in medium not added placental extract, as well as placental extract added in the medium stimulation index increased 1.08 or splenocyte division by 0.8 times or almost the same than those wells with culture treated with mitogen only. Semi-purification placental protein was inhibition on 1% carrageenan induced rat paw edema and it means bovine placental extract effectively reduce acute inflammation.Үнээний эхэсийн хандны үрэвслийн эсрэг идэвх болон дархлаанд үзүүлэх нөлөөг судласан дүнЭхэс гэх эмийн түүхий эдийг дэлхийн олон эрдэмтэд бүтэц, физиологи, найрлага, биологийн идэвхт пептид ялган авч тэдгээрийн эмчилгээний идэвхийг судлаж улмаар хүн, мал, амьтны эрүүл мэнд, гоо сайханд хэрэглэх эм, биобэлдмэл гарган авах чиглэлээр олон талаас нь судалгаа, туршилтын ажлыг хийж байна. Энэхүү судалгааны зорилго нь үнээний эхэсээс хагас цэвэршүүлсэн уураг ялган антиоксидант идэвх, дархлаанд үзүүлэх нөлөөг in vitro орчинд судлах, үрэвслийн эсрэг идэвхийг туршилтын амьтны эмгэг загварт туршихад оршино. Эхэсийн ханд бэлтгэхдээ фосфатын буфер, ТрисHCl, нэрмэл усаар жигдрүүлж (гомогенизаци), цаашид тус бүр нэрмэл ус, ацетон, этанол, сульфат аммоны давс ашиглан 4 аргаар тундасжуулж хандлан гель хроматорафийн аргаар хагас цэвэршүүлсэн уураг ялган авав. Хагас цэвэршүүлсэн уургийн антиоксидант идэвхийг DPPH чөлөөт радикал саармагжуулах урвалаар, дархлаанд үзүүлэх нөлөөг MTT assay kit ашиглан, үрэвслийн эсрэг идэвхийг 1%-ийн Каррагининаар өдөөсөн хархны сарвуунд шүүдэст үрэсвлийн эмгэг загвар үүсгэн тус тус судлав. Хагас цэвэршүүлсэн уургийн концентрацийг тодорхойлоход фосфатын буферээр жигдрүүлж, ацетоноор тундасжуулсан хувилбарт уургийн хэмжээ хамгийн их 6217.5 мкг/мл, фосфатын буферээр жигдрүүлж, сульфат аммоны давсаар тундасжуулахад уургийн хэмжээ хамгийн бага 1477.4 мкг/мл байв. Үнээний эхэсийн хандны DPPH чөлөөт радикал саармагжуулах идэвх 55.1±1.2%, стандарт бодис Рутин 67.1±1.2% байсан бол дархлаанд үзүүлэх нөлөө үнээний эхэсийн ханд нэмсэн бүлгийг хяналтын бүлэгтэй харьцуулхад эс хуваагдлын индекс 1.45 буюу 1.5 дахин их, митоген нэмсэн бүлэгтэй харьцуулахад эс хуваагдлын индекс 1.08 буюу 0.8 дахин их буюу бараг адил хэмжээнд байлаа. 1%-ийн Каррагининаар үүсгэсэн хархын сарвууны шүүдэст үрэвсэлд үнээний эхэсээс ялгасан хагас цэвэршүүлсэн уураг нь үрэвслийн хаванг бууруулах нөлөөтэй ба үнээний эхэсийн ханд нь үрэвслийн эсрэг идэвхтэй байгаа нь тогтоогдов. Түлхүүр үг: Уураг, каррагинин, антиоксидантидэвх,шүүдэст үрэвсэл, хроматограф